2017
DOI: 10.1053/j.jvca.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Longitudinal Strain In Left Ventricular Assist Device Surgery–A Retrospective Cohort Study

Abstract: Objectives Right ventricular (RV) failure is common after left ventricular assist device (LVAD) surgery and is associated with higher mortality. Measurement of longitudinal RV strain using speckle-tracking technology is a novel approach to quantify RV function. We hypothesized that depressed peak longitudinal RV strain measured by intraoperative transesophageal echocardiography (TEE) examinations would be associated with adverse outcomes after LVAD surgery. Design Retrospective Cohort Study. Setting Tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…6 Beck et al used a similar GLS cutoff value; their study failed to focus on RVF, focusing instead on composite outcomes, and reported no prognostic utility with TEE-derived RV GLS. 3 However, patients with poor outcomes had lower RV GLS, and a larger sample size may have reached statistical significance. Upon analyzing the outcomes of Beck et al by further focusing on RVF ( 4 14 days of inotropic support, need for mechanical RV support), 16 of 57 patients (28%) developed RVF and had a GLS r -9.2%, a finding akin to the report by Grant et al, showing the potential prognostic value of intraoperative transesophageal STE-derived RV GLS.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…6 Beck et al used a similar GLS cutoff value; their study failed to focus on RVF, focusing instead on composite outcomes, and reported no prognostic utility with TEE-derived RV GLS. 3 However, patients with poor outcomes had lower RV GLS, and a larger sample size may have reached statistical significance. Upon analyzing the outcomes of Beck et al by further focusing on RVF ( 4 14 days of inotropic support, need for mechanical RV support), 16 of 57 patients (28%) developed RVF and had a GLS r -9.2%, a finding akin to the report by Grant et al, showing the potential prognostic value of intraoperative transesophageal STE-derived RV GLS.…”
mentioning
confidence: 96%
“…1,2 CF-LVAD therapy has accelerated globally as both a bridge-to-transplantation and destination therapy and has demonstrated superiority over pharmacotherapy and cardiac resynchronization therapy in heart failure patients. [1][2][3][4][5] Despite the survival benefits of CF-LVAD therapy, a significant proportion of patients develop perioperative complications, mainly due to right ventricular dysfunction (RVD) or right ventricular failure (RVF) after CF-LVAD placement. [1][2][3][4][5][6] RVD/RVF occurrence may be secondary to changes in the geometry and function of the right ventricle induced in part by the LVAD (increased circulatory volume and excessive left ventricular decompression) and fluid management and may result in low CF-LVAD output, right heart failure, and multisystem organ failure.…”
mentioning
confidence: 99%
See 3 more Smart Citations